Design of cab seat suspension system for construction machinery based on negative stiffness structure. (August 2021) - Liao, Xin; Du, Xiaofei; Li, Shaohua
In order to improve the vibration isolation performance of cab seat and ride comfort of the driver, a seat suspension structure of construction machinery cab is proposed based on negative stiffness structure (NSS) in this paper. The influences of different parameters of suspension system on dynamic stiffness are analyzed. The configuration parameter range of suspension system is obtained. Then, the nonlinear dynamic equation of the seat suspension system is established and the NSS optimization model is proposed. The vibration transmissibility characteristics of suspension structure are analyzed by different methods. The results show that the displacement and acceleration amplitude of optimized seat suspension system are obviously reduced, and the VDV and RMS in the vertical vibration direction for the seat are respectively decreased by 87% and 86%. The vibration transmissibility rate SEAT and the T trans are both decreased. Moreover, the peak frequencies of the vibration transmitted to the driver are not near the key frequency values which are easy to cause human discomfort. It indicates that the design of seat suspension system has no effect on the health condition of the driver after being vibrated. The advantages of vibration isolation performance of the designed NSS suspension system are demonstrated, improving the driver's ride comfort and the working environment.